Quality strategy for research and development - Shiu, Ming-Li (Wiley, 2013)
Providing readers with a clear, useful framework for systems engineering, this book integrates the Japanese and Western perspectives of Quality Function Deployment (QFD) and relates its unique framework to current, widely adopted philosophies of quality assurance. Featuring real-world case studies, more than 30 tables, and over 70 figures, this essential guide identifies key issues and proposes improvements in current models of quality engineering. In-depth coverage of testing and inspections, production operations management, product/process design, and energy optimization with developed technology round out this resource and makes it mandatory reading